2008
DOI: 10.1007/s11199-007-9377-z
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment and Powerlessness: A Closer Look at the Relationship Between Feminism, Body Image and Eating Disturbance

Abstract: Objectification Theory (Frederickson & Roberts, 1997) states that women's bodies are viewed as objects to be evaluated and this societal objectification may lead to self-objectification when women view their own bodies as objects. The current study theorized that empowerment is an important factor in reducing self-objectification. Although empowerment is a central tenet of feminist theory, this study is the first to examine the relationship between empowerment, feminism, and body image and eating disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 49 publications
2
36
0
3
Order By: Relevance
“…Because women are socialized to experience their efforts to monitor and improve their physical appearance as self-chosen or "natural" (Costanzo 1992;Fredrickson and Roberts 1997), many women who are at risk for eating disorders or undergoing eating disorders treatment are unlikely to identify self-objectification as a problem because they are unaware that it is a potentially harmful, socially constructed form of self-perception that contributes to feelings of powerlessness over one's own body (Peterson et al 2008) and interferes with positive psychological functioning (Mercurio and Landry 2008). This occurs in spite of evidence demonstrating markedly high levels of selfobjectification among women in eating disorders treatment programs (Calogero et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because women are socialized to experience their efforts to monitor and improve their physical appearance as self-chosen or "natural" (Costanzo 1992;Fredrickson and Roberts 1997), many women who are at risk for eating disorders or undergoing eating disorders treatment are unlikely to identify self-objectification as a problem because they are unaware that it is a potentially harmful, socially constructed form of self-perception that contributes to feelings of powerlessness over one's own body (Peterson et al 2008) and interferes with positive psychological functioning (Mercurio and Landry 2008). This occurs in spite of evidence demonstrating markedly high levels of selfobjectification among women in eating disorders treatment programs (Calogero et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One can only wonder if the women in this study would see these efforts as a waste of energy, or if they would perceive the time spent in such efforts as having some value, as an important part of their process of becoming less obsessed with their bodily appearance. Peterson et al (2008) have shown that feelings of empowerment may decrease a woman's likelihood of internalizing society's messages about beauty and developing schemas that highlight the importance of appearance. Self-empowerment has also been said to help in reducing self-objectification and body image disturbances in women.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The feminist perspective reaffirms the declaration that a woman's self-worth, ability, and livelihood are not centred on her physical appearance. Peterson, Grippo, and Tantleff-Dunn (2008) proposed that acquiring a feminist identity should protect women from negative feelings about their bodies, given that feminist women are more attuned to recognizing and resisting oppressive cultural messages. For example, women are encouraged to refute the message of the importance of thinness, question traditional societal and cultural roles, and develop more empowering selfdefinitions based on other attributes such as their intelligence or creativity.…”
Section: Interpersonal Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have been conducted using the scale as a whole (e.g. Peterson, Grippo, & Tantleff‐Dunn, 2008) as well as specific subscales (Dalgard et al., 2006). To attain further evidence for the construct validity of ES and to support the findings obtained by Rogers et al.…”
Section: Methodsmentioning
confidence: 99%